Factors that contribute decision to quit among the employees of Binary Gains Sdn Bhd / Norizam Baharudin - Baharudin, Norizam (Faculty of Business and Management, 2010)
Binary Gains Sdn Bhd is a locally owned company that brings its customers 6 years of professional vending experience. The company started in 2003, has grown into one of the largest and most in the provision of vending machine services, can drink, hot beverages and cold drink and office coffee services to commercial and public organizations. According to the Manpower Analysis of 2009, there will be more than two employees resign within four months in the organization. The main objective of this research is to find out the relationship between factors that contributes to the intention to quit and decision to quit and the factor that contribute most to the decision to quit among employees of Binary Gains Sdn Bhd. The factors of intention to quit consists of four factors that are individual understanding about job position and job description, organization management, commitment, and involvement from supervisor, individual feeling towards job and individual satisfaction towards working environment. Convenience sampling technique has been used as a sampling technique to get the data for this research where the population for this research was the employees that currently working at Binary Gains Sdn Bhd. About 18respondents were involved in this research to help to accomplish this research by answering questionnaires that had been distributed to them. All data that had been collected through the questionnaire were analyzed systematically by Statistical Package for Social Science (SPSS). The conclusion of this study was the outcome from the data analysis and findings. Through the research, it shows based on Pearson Correlation Analysis and Descriptive Statistic, a clear finding and results were observed. The findings showed that the individual feeling towards job and individual satisfaction towards working environment has a relationship with the decision to quit and the factor that contributes most to decision to quit is individual satisfaction towards working environment.